2019
DOI: 10.1038/s41598-019-44342-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motor versus Sensory Nerve Autografts on Regeneration and Functional Outcomes of Rat Facial Nerve Reconstruction

Abstract: Cranial nerve injury is disabling for patients, and facial nerve injury is particularly debilitating due to combined functional impairment and disfigurement. The most widely accepted approaches for reconstructing nerve gap injuries involve using sensory nerve grafts to bridge the nerve defect. Prior work on preferential motor reinnervation suggests, however, that motor pathways may preferentially support motoneuron regeneration after nerve injury. The effect of motor versus sensory nerve grafting after facial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The phenotypic memory of the SCs after denervation might play a role in PMR, since graft modality used to repair a nerve resection influences the outcome of axonal regeneration. While some studies could not find improved motor regeneration when the femoral or the facial nerve were repaired with modality-matched grafts [ 68 , 69 ], others found that motor axons from the sciatic and tibial nerve regenerated better through a ventral root or a motor nerve than through a sensory graft [ 57 , 70 , 71 ]. The selective effect may be partially sustained in predegenerated grafts.…”
Section: Motor and Sensory Schwann Cellsmentioning
confidence: 99%
“…The phenotypic memory of the SCs after denervation might play a role in PMR, since graft modality used to repair a nerve resection influences the outcome of axonal regeneration. While some studies could not find improved motor regeneration when the femoral or the facial nerve were repaired with modality-matched grafts [ 68 , 69 ], others found that motor axons from the sciatic and tibial nerve regenerated better through a ventral root or a motor nerve than through a sensory graft [ 57 , 70 , 71 ]. The selective effect may be partially sustained in predegenerated grafts.…”
Section: Motor and Sensory Schwann Cellsmentioning
confidence: 99%
“…Thoracodorsal nerve or portions of the femoral nerve have been investigated as donor areas for NG. 18 19 20 Motor nerves as VNT have also been described either alone or as a part of composite free tissue transfers for facial defects. 21 22 …”
Section: Discussionmentioning
confidence: 99%
“…Also, when the nerve gap is larger than 5-mm, nerve interposition or "cable graft" procedures are commonly performed. However, the recovery of the transected or resected nerve after reconstruction of the nerve defect is not satisfactory 53 . Thus, the treatment of functional recovery after facial nerve axotomy is still a major problem.…”
Section: Discussionmentioning
confidence: 99%